Kyŏnghŏ Sŏngu and the Existential Dimensions of Modern Korean Buddhism - Bag, Jin yeong (Journal of Korean religions, 2019)
What would be the attraction of religion in modern times? And how do religious practitioners come to encounter the religious dimensions of their existence? This article examines Kyŏnghŏ Sŏngu’s Buddhism with a focus on his struggle to define human existential reality. I will examine his life story and identify the nature of the religiosity of Kyŏnghŏ’s Buddhism and consider the meaning of religious practice in our time. By doing so, I propose to reconsider the beginning of modern Korean Buddhism. The beginning of modern Korean Buddhism should not be understood as the founding or revival of a certain sectarian identity of Korean Buddhism. Instead, through thematic approaches to what Kyŏnghŏ’s life and Buddhism meant in terms of religious practice and how this religious practice was related to other Buddhist movements of the time, I propose to understand modern Korean Buddhism through the religious and socio-historical reality of modern Korea.